2023
DOI: 10.1002/art.42677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B Cell Depletion by CD19‐Targeted Chimeric Antigen Receptor T Cells in a Murine Model of Systemic Sclerosis

Jérôme Avouac,
Anne Cauvet,
Cindy Orvain
et al.

Abstract: ObjectiveTo study the tolerance and efficacy of two B cell depletion strategies, including one with CD19‐targeted chimeric antigen receptor (CAR) T cells, in a preclinical model mimicking the severe lung damages observed in systemic sclerosis (SSc).MethodsB cell depletion strategies were evaluated in the Fra‐2 transgenic (Tg) mouse model. We considered a first group of 16 untreated mice, a second group of 15 mice receiving a single dose of anti‐CD20 monoclonal antibody (mAb) and a third group of 8 mice receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Disease severity was assessed using a ten point scale as previously reported 19,20 . One point was given for the presence of blepharitis, alopecia, skin lesions, abnormal fur texture, hepatomegaly, hunched posture, or impaired mobility.…”
Section: Soquelitinib Is Effective In a Mouse Model Of Systemic Scler...mentioning
confidence: 99%
See 2 more Smart Citations
“…Disease severity was assessed using a ten point scale as previously reported 19,20 . One point was given for the presence of blepharitis, alopecia, skin lesions, abnormal fur texture, hepatomegaly, hunched posture, or impaired mobility.…”
Section: Soquelitinib Is Effective In a Mouse Model Of Systemic Scler...mentioning
confidence: 99%
“…This mutation results in widespread inflammation, vasculopathy, pulmonary fibrosis, and pulmonary hypertension. The mice develop vascular injury which precedes fibrosis as is seen in systemic sclerosis 19,20 . The model and techniques for its assessment have been previously described 19,20 .…”
Section: Soquelitinib Is Effective In a Mouse Model Of Systemic Scler...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ASyS case mentioned earlier [ 13 ] exemplifies this complexity, wherein enhanced CD8 + T cells were detected in circulation following CAR-T treatment, leading to the incorporation of additional T cell suppressive drugs due to concerns about potential relapse. A recent report of the failure of murine CD19-targeted CAR-T therapy on an SSc animal model also suggested that CAR-T design should be consistent with disease pathogenesis [ 49 ]. The study used a Fra-2 transgenic mouse model, which could well mimic the fibrosis and vasculopathy of SSc but lacks the typical autoimmune response [ 50 , 51 ].…”
Section: Advantages Over Existing Immunosuppresive Therapies and Main...mentioning
confidence: 99%
“…The study used a Fra-2 transgenic mouse model, which could well mimic the fibrosis and vasculopathy of SSc but lacks the typical autoimmune response [ 50 , 51 ]. Although CD19-targeted CAR-T combined with anti-CD20 monoclonal antibody achieved deeper B cell depletion in the peripheral blood and lungs of Fra-2 mice than anti-CD20 monoclonal antibody alone, it did not improve overall outcomes, and even worsened the pulmonary fibrosis and pulmonary hypertension [ 49 ]. This is partly because B cells do not play a key role in the pathogenesis of Fra-2 transgenic mice, verified by the result that the anti-CD20 monoclonal antibody group did not show a significant difference compared with the control group.…”
Section: Advantages Over Existing Immunosuppresive Therapies and Main...mentioning
confidence: 99%